The clustering of H β + [O iii] and [O ii] emitters since z ∼ 5: dependencies with line luminosity and stellar mass. Issue 3 (14th April 2018) - Khostovan, A A; Sobral, D; Mobasher, B; Best, P N; Smail, I; Matthee, J; Darvish, B; Nayyeri, H; Hemmati, S; Stott, J P
ABSTRACT: We investigate the clustering properties of ∼7000 H β + [O iii ] and [O ii ] narrowband-selected emitters at z  ∼ 0.8–4.7 from the High- z Emission Line Survey. We find clustering lengths, r 0, of 1.5–4.0 h −1  Mpc and minimum dark matter halo masses of 10 10.7–12.1 M⊙ for our z = 0.8–3.2 H β + [O iii ] emitters and r 0 ∼ 2.0–8.3 h −1  Mpc and halo masses of 10 11.5–12.6 M⊙ for our z = 1.5–4.7 [O ii ] emitters. We find r 0 to strongly increase both with increasing line luminosity and redshift. By taking into account the evolution of the characteristic line luminosity, L ⋆ ( z ), and using our model predictions of halo mass given r 0, we find a strong, redshift-independent increasing trend between L / L ⋆ ( z ) and minimum halo mass. The faintest H β + [O iii ] emitters are found to reside in 10 9.5 M⊙ haloes and the brightest emitters in 10 13.0 M⊙ haloes. For [O ii ] emitters, the faintest emitters are found in 10 10.5 M⊙ haloes and the brightest emitters in 10 12.6 M⊙ haloes. A redshift-independent stellar mass dependency is also observed where the halo mass increases from 10 11 to 10 12.5 M⊙ for stellar masses of 10 8.5 to 10 11.5 M⊙, respectively. We investigate the interdependencies of these trends by repeating our analysis in a L line − M star grid space for our most populated samples (H β + [O iii ] z = 0.84 and [O ii ] z = 1.47) and find that the line luminosity dependency is stronger than the stellar mass dependency on halo mass. For L  >  L ⋆ emitters at all epochs, we find a relatively flat trend with halo masses of 10 12.5–13 M⊙, which may be due to quenching mechanisms in massive haloes that is consistent with a transitional halo mass predicted by models.